Pengembangan Aparatur Desa Wangunharja Melalui Bimbingan Teknis Coaching dan Counseling - Anindita, Nadiarani; Maasir, Lidia; Annisa, Yayuk Nur (Setia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2023)
The aim of this coaching and counseling technical guidance activity is to enhance the competency of the Wangunharja Village Apparatus in the field of coaching & counseling. It is hoped that this activity will foster advanced village governance practices, cultivating village cadres as leaders who have good knowledge, attitudes and skills. The research used Participatory Learning and Action method. This activity is carried out by emphasizing lectures, discussions, brainstorming and simulations conducted interactively with group members, complemented by real-world actions or activities relevant to community empowerment material through coaching & counseling. The outcomes of community service activities aligned with the established plans. Village officials were receptive and enthusiastic about training workshops and exhibited tangible improvements in their knowledge, attitudes, and skills. The output of this technical guidance activity is the preparation of coaching and counseling guidelines for Wangunharja village officials.